Value of CT angiography in anterior circulation large vessel occlusive stroke: Imaging findings, pearls, and pitfalls. Issue 7 (July 2015) - Power, Sarah; McEvoy, Sinead H.; Cunningham, Jane; Ti, Joanna P.; Looby, Seamus; O'Hare, Alan; Williams, David; Brennan, Paul; Thornton, John
Highlights: Site of occlusion determines potential collateralization routes and impacts outcome. Multifocality of arterial occlusion is common, seen in approximately 20% of cases. ICA false occlusion sign can be seen in setting of ICA stenosis or carotid T occlusion. False patency sign: hyperdense thrombus/calcified occlusive plaque misinterpreted as patent vessel. Additional abnormalities on CTA may infer stroke mechanism or alter decision making. Abstract: Hyperacute stroke imaging is playing an increasingly important role in determining management decisions in acute stroke patients, particularly patients with large vessel occlusive stroke who may benefit from endovascular intervention. CT angiography (CTA) is an important tool in the work-up of the acute stroke patient. It reliably detects large occlusive thrombi in proximal cerebral arteries and is a quick and highly accurate method in identifying candidates for endovascular stroke treatment. In this article we review the imaging findings on CTA in acute large vessel occlusive stroke using a pictorial case based approach. We retrospectively reviewed CTA studies in 48 patients presenting with acute anterior circulation large vessel occlusive stroke who were brought for intra-arterial acute stroke intervention. We discuss and illustrate patterns of proximal intracranial arterial occlusion, collateralization to the occluded territory, as well as reviewing some important pearls, pitfalls and teaching points in CTA assessment of the acute stroke patient. Performed from the level of the aortic arch CTA also gives valuable information regarding the state of other vessels in the acute stroke patient, identifying additional significant vascular stenoses or occlusions, and as we illustrate, can demonstrate other clinically significant findings which may impact on patient management and outcome.